Mn pre-intercalated hydrated vanadium pentoxide activated by nitrogen plasma for enhanced zinc ion storage. (July 2023) - Qian, Jinchen; You, Yurong; Fan, Zixuan; Liu, Xingyu; Tang, Jun; He, Wei; Sun, ZhengMing
Abstract: Hydrated vanadium pentoxide is a promising cathode candidate for zinc ion batteries due to its open-framework crystal structure and high capacity. Nevertheless, the strong electrostatic interaction between the inserted Zn 2+ and host cause sluggish reaction kinetics and limited cycle performance. Herein, an N doped Mn pre-intercalated hydrated vanadium pentoxide (N-MVO) is successfully synthesized by nitrogen plasma treatment. The pre-intercalated Mn and strong VN stabilizes the host structure, and the oxygen vacancies caused by N introduction weaken the interaction between Zn 2+ and host, facilitate the insertion/extraction of the Zn 2+, resulting in superior rate capacity and long cycle stability. Remarkably, at a current density of 5 A g −1, the cell with the N-MVO cathode demonstrates a specific capacity of 197 mAh g −1 with retention of 88 % over 2000 cycles. HIghlights: N is introduced by nitrogen plasma treatment in Mn pre-intercalated V2 O5 ·nH2 O. Plasma treated sample shows superior rate capacity and long cycle stability. N introduction weakens the interaction between Zn 2+ and host.